The Legal Standing of Land Nominee Agreements from the Perspective of Lawful Cause - Shulkhantika, Deyosi Faza; Hastuti, Luthfiyah Trini; Isharyanto, Isharyanto (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The practice of borrowed-name agreements in land transactions in Indonesia raises significant concerns regarding contractual validity and legal certainty, particularly when such arrangements are employed to circumvent statutory prohibitions on land ownership. The core issue lies in the discrepancy between the formal structure of the agreement and its substantive purpose, which contravenes agrarian law. This study examines the legal implications of failing to satisfy the requirement of a lawful cause in borrowed-name agreements, formulates a juridical–conceptual framework for assessing their validity through an integration of the doctrine of lawful cause and mandatory principles of agrarian law, and delineates the limits of contractual freedom in land ownership. Employing normative legal research methods, including conceptual analysis, statutory interpretation, and case law review, the study finds that borrowed-name agreements are legally invalid when their purpose is to evade agrarian restrictions, notwithstanding their formal compliance with contractual requirements. The study concludes that the doctrine of lawful cause remains a crucial evaluative instrument for safeguarding the balance between freedom of contract, legal certainty, justice, and public order within the national legal system.